Aligning Economic and Ecological Priorities: Conflicts, Complementarities, and Regulatory Frictions. (30th August 2017) - Herrera, Guillermo E.; Evans, Keith S.; Lewis, Lynne Y.
Abstract : Four key policy challenges, framed here as dichotomies, are commonly associated with attempts to improve the use of natural resources in the socioecological commons. These dichotomies present tradeoffs when addressing market failures and in general seem to suggest the need to settle for second-best outcomes rather than first-best outcomes identified in stylized models. Citing examples, we argue that these models, while illustrating these dichotomies, also suggest means for circumventing them, and perhaps provide a degree of optimism about prospective outcomes in socioecological systems.